Ezekiel a commentary - Eichrodt, Walther, 1890-1978; Quinn, Coslett (London, UK SCM, 1970)
Includes bibliographical references.
Originally published 1965-66, Gottingen, Vandenhoeck and Ruprecht : Der Prophet Hesekiel (Das Alte Testament Deutch 22/1-2)
Keywords: Bible. O.T. Ezekiel -- commentaries